2021
DOI: 10.1371/journal.pone.0259772
|View full text |Cite
|
Sign up to set email alerts
|

Variation in tube voltage for pediatric neck 64VCT: Effect on radiation dose and image quality

Abstract: Exposure to ionizing radiation can cause cancer, especially in children. In computed tomography (CT), a trade-off exists between the radiation dose and image quality. Few studies have investigated the effect of dose reduction on image quality in pediatric neck CT. We aimed to assess the effect of peak kilovoltage on the radiation dose and image quality in pediatric neck multidetector-row CT. Measurements were made using three phantoms representative of children aged 1, 5, and 10 years, with tube voltages of 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…For example, a previous study found that by reducing the peak potential from 120 to 80 kVp, multidetector-row computed tomography may reduce the effective radiation dose by 68.58% and can maintain uncompromising image quality in pediatric neck Ct examinations (51). another study demonstrated that automatic current selection setup was more effective than the fix tube current according to the ALARA principle.…”
Section: Enhancing Medical Knowledge and Education Regarding Radiatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a previous study found that by reducing the peak potential from 120 to 80 kVp, multidetector-row computed tomography may reduce the effective radiation dose by 68.58% and can maintain uncompromising image quality in pediatric neck Ct examinations (51). another study demonstrated that automatic current selection setup was more effective than the fix tube current according to the ALARA principle.…”
Section: Enhancing Medical Knowledge and Education Regarding Radiatio...mentioning
confidence: 99%
“…For CT scans, there are several techniques, including the reduction of tube voltage, the use of dual-source CT for high-pitch helical scanning, modulation of the tube current and optimization of the scan length which have been used to reduce radiation doses ( 50 ). For example, a previous study found that by reducing the peak potential from 120 to 80 kVp, multidetector-row computed tomography may reduce the effective radiation dose by 68.58% and can maintain uncompromising image quality in pediatric neck CT examinations ( 51 ). Another study demonstrated that automatic current selection setup was more effective than the fix tube current according to the ALARA principle.…”
Section: Specific Recommendations and Measures For Reducing X-ray Rad...mentioning
confidence: 99%